ANALISIS PENDAPATAN PETANI KARET POLA SWADAYA DI KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Siregar, Masrayani; Maharani, Evy; Edwina, Susy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Pattern swadaya farmerâ€™s is development rubber plantation by society conducted of farmer self supporting is not intervention government. The purpose of this research is to analyze the income of rubber farmers swadaya pattern and eficiency farming of rubber farmers swadaya in pangkalan kuras sub-district pelalawan regency with consideration that basis most living of resident is rubber farmer cleanse sub-district. The research for 5 monts, started on February until August 2015. The analysis used is income analysis, return cost ratio (RCR) analyse. The result of research showed that net income rubber farmer swadaya pattern is Rp14.959.837,55 with the total cost swadaya farmers is Rp14.323.227,56 by ha/year and the total revenue swadaya farmers is Rp29.283.065,11 ha/year. The average value RCR of rubber farmers swadaya pattern is 1,59 its mean the value that are profitable with value RCR>1. Â Keywords : Income, eficiency of farming, swadaya pattern